A preliminary investigation on improving preschoolers’ language and mathematical abilities via a working memory training program. - Goh, Rachel Rui Xue (2012)
The current study is aimed at exploring the effectiveness of a short working memory training programme, as well as examining the association of working memory and school readiness in Singaporean preschoolers. Five year olds (N = 17) were tested with one executive function measure and two school readiness measures, measuring working memory, prereading and premathematical skills. The preschoolers joined the current study’s short two-session working memory training programme as well. Although non-parametric tests showed that preschoolers’ working memory and school readiness scores did not improve after the training programme; consistent with past research, results showed positive and moderate bivariate correlations between working memory and the two measures of school readiness.